KONSEPSI ALTERNATIF MAHASISWA PADA RANAH MEKANIKA: ANALISIS UNTUK KONSEP IMPETUS DAN KECEPATAN BENDA JATUH - Syuhendri . (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2014)
Has conducted research on student alternative conceptions diagnose concept impetus and velocity falling objects. Subjects were 73 students of physical education a public university in South Sumatra. Data collected by the test (18 items of the Force Concept Inventory), interviews, and observation of learning. From the results, an alternative conception of the respondents on the impetus in the form of 1) a moving object has derived impetus from the blow given (59.93 %), 2) objects owned impetus is lost or recovered during the movement of objects (30.14 %), 3) owned impetus slowly lost objects (40.87 %) , 4) impetus objects appear some time after the cause no (19.41 %) , and 5) impetus also occurs in a circular motion (54.11 %); and the speed of falling objects such as heavy objects fall faster (79.45 %). These results indicate that the respondents have a strong misconception that the force required to maintain the motion of objects and the mass or weight of the object affect the speed of a falling object . It is advisable to carry out the conceptual change theory -based learning on the subject-matter of mechanics to remediate non - scientific concepts such .